Clinico-Pathological Changes in Hemoprotozoan Infections in Dogs - Raval, Jeetendra; Bhoi, Dhiren; Parmar, Hitesh; Vihol, Priti; Prajapati, Harshil; Patel, Utpal (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A total of 1200 blood samples were examined from the dogs for screening hemoprotozoan infection in and around Navsari district of  south Gujarat, India. Out of these cases 18 were found positive for Trypanosoma cruzi, 27 for Dirofilaria immitis and 8 for Hepatozoon  canis. The clinico-pathological changes included gastrointestinal and haematological disturbances including anaemia, ascites, fever,  cardiomyopathy and altered serum urea and creatinine values. The information derived on hemoprotozoan diseases could be helpful  for further subsequent diagnostic, preventive and therapeutic care in South Gujarat.
Keywords: Clinico-pathology; Dogs; Hemoprotozoa